2018
DOI: 10.3389/fncel.2018.00355
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Oxytocin Treatment Ameliorates Autistic-Like Behaviors and Oxytocin Deficiency in Valproic Acid-Induced Rat Model of Autism

Abstract: Autism spectrum disorder (ASD) is characterized by impaired social communication and repetitive/stereotyped behaviors. The neuropeptide oxytocin (OXT) plays a critical role in regulating social behaviors in the central nervous system, as indicated in both human and animal studies. We hypothesized that central OXT deficit is one of causes of etiology of ASD, which may be responsible for the social impairments. To test our hypothesis, central OXT system was examined in valproic acid (VPA)-induced rat model of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 121 publications
(158 reference statements)
6
46
0
Order By: Relevance
“…Our ndings in this phase were also in agreement with Dai et al. [88] In the social novelty phase of that test, all VPA-injected rats demonstrated an unwillingness to establish new social relationships. Increased marble burial activity in all VPA-injected rats indicated enhanced repetitive behavior.…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings in this phase were also in agreement with Dai et al. [88] In the social novelty phase of that test, all VPA-injected rats demonstrated an unwillingness to establish new social relationships. Increased marble burial activity in all VPA-injected rats indicated enhanced repetitive behavior.…”
Section: Discussionsupporting
confidence: 92%
“…It was suggested that these effects may reflect differences in the neuronal organisation and activation sites of oxytocin between control and oxytocin‐null rodents. Furthermore, Dai et al 11 reported that prenatally exposed VPA rat pups had less oxytocin immune‐reactive cells, and administration of oxytocin to these pups several times during early PND showed an increase in the number of USV calls. Thus, oxytocin has a different effect on vocalisation by maternal separation in the control group compared to VPA mice pups.…”
Section: Discussionmentioning
confidence: 99%
“…Penagarikano et al 10 reported that acute administration of oxytocin improves social behavioural deficits of contactin‐associated protein‐like 2 (CNTNAP‐2) mutant adult mice and showed that chronic early postnatal treatment with oxytocin leads to lasting recovery of social behaviour. Furthermore, Dai et al 11 showed that early neonatal oxytocin treatments had a long‐term therapeutic effect on autistic behaviours in prenatally exposed VPA rats. Thus, oxytocin treatment during early developmental stages may have a therapeutic effect on autistic behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms of genes encoding the proteins and related regulatory factors such as the OXT-NPI (encoding the OXT prepropeptide), OXTR or CD38 genes (involved in OXT release in the brain), are associated with social deficits and repetitive behavior and have been reported in autistic populations [33,34]. Similarly, findings in animal models relate impairments of the OXT system to ASD symptoms such as social memory [35] restricted interests to novelty [36] or social communication and interaction [37,38].…”
Section: Introductionmentioning
confidence: 99%